Review on investigating the possibility of local hidden variable theories-quantum teleportation - Addo, Dorcas Attuabea; Abel, Steven; Ansah, Richard Kwame; Nkrumah, Isaac (International Journal of Advanced Mathematical Sciences, 2018)
The core of the paper was to investigate the possibility of local hidden variable theory and its application in quantum teleportation. We reviewed literature on the Bell's inequality which is necessary for quantum teleportation. Quantum teleportation utilises a single-particle entangled state which can be successfully achieved by the application of the locality assumption which leads to Bell's inequality. A violation of the Bell's inequality signifies the nonlocal nature of a single particle useful for quantum teleportation.